(3JfHjg GdaGFRjf aj CaYGd GdUGdMjfs - (3YHO Gddg Hf eMeO GdaGVds ((3SYjO Hf eMeO fUQjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO jbhd GdYHO YHO Gddg Hf eMeO GdaGVd hHYO agPG cJGH UZjQcKjQ GdbOQ hSejJg JfHjg GdaGFRjf aj CaYGd GdUGdMjfs
(3BNQgG (B:s
(3hUGQhG ChdjGA ef GdPjf dG Nha Ydjge hdG ge jMRfhfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs